Fashion Victim - Akhtar, Amina ([Place of publication not identified] : Crooked Lane Books, 2018)
A darkly thrilling take on the fashion world, #FashionVictim is Heathers meets The Devil Wears Prada for the millennial generation.
Keywords: Fashion editors -- New York (State); New York; Fiction; Murder -- Fiction; Adult Fiction; Electronic books